Hereditary Sensory and Autonomic Neuropathy 2B Caused by a Novel RETREG1 Mutation (c.765dupT) and Paternal Uniparental Isodisomy of Chromosome 5 - Park, Geun-Young; Jang, Dae-Hyun; Lee, Dong-Woo; Jang, Ja-Hyun; Joo, Joungsu (Frontiers in Genetics, 2019)
Hereditary sensory and autonomic neuropathy (HSAN) 2B is a rare disease and has been reported mostly in offsprings of consanguineous parents. Here we report the case of a patient born to non-consanguineous parents who was diagnosed with HSAN 2B caused due to a novel frameshift mutation (NM_001034850.2: c.765dupT/p.Gly256TrpfsTer7) in the RETREG1 gene and paternal uniparental isodisomy of chromosome 5. Uniparental isodisomy of chromosome 5 is also a rare condition, and these two rare events lead to homozygous expression of a recessive mutation, as in the present case. Clinicians should be aware that autosomal recessive disorders due to homozygous variants can occur because of uniparental disomy in offsprings of non-consanguineous parents.